The binding site for neohesperidin dihydrochalcone at the human sweet taste receptor - Winnig, Marcel (BioMed Central, 2007)
BACKGROUND: Differences in sweet taste perception among species depend on structural variations of the sweet taste receptor. The commercially used isovanillyl sweetener neohesperidin dihydrochalcone activates the human but not the rat sweet receptor TAS1R2+TAS1R3. Analysis of interspecies combinations and chimeras of rat and human TAS1R2+TAS1R3 suggested that the heptahelical domain of human TAS1R3 is crucial for the activation of the sweet receptor by neohesperidin dihydrochalcone. RESULTS: By mutational analysis combined with functional studies and molecular modeling we identified a set of different amino acid residues within the heptahelical domain of human TAS1R3 that forms the neohesperidin dihydrochalcone binding pocket. Sixteen amino acid residues in the transmembrane domains 2 to 7 and one in the extracellular loop 2 of hTAS1R3 influenced the receptor's response to neohesperidin dihydrochalcone. Some of these seventeen residues are also part of the binding sites for the sweetener cyclamate or the sweet taste inhibitor lactisole. In line with this observation, lactisole inhibited activation of the sweet receptor by neohesperidin dihydrochalcone and cyclamate competitively, whereas receptor activation by aspartame, a sweetener known to bind to the N-terminal domain of TAS1R2, was allosterically inhibited. Seven of the amino acid positions crucial for activation of hTAS1R2+hTAS1R3 by neohesperidin dihydrochalcone are thought to play a role in the binding of allosteric modulators of other class C GPCRs, further supporting our model of the neohesperidin dihydrochalcone pharmacophore. CONCLUSION: From our data we conclude that we identified the neohesperidin dihydrochalcone binding site at the human sweet taste receptor, which overlaps with those for the sweetener cyclamate and the sweet taste inhibitor lactisole. This readily delivers a molecular explanation of our finding that lactisole is a competitive inhibitor of the receptor activation by neohesperidin dihydrochalcone and cyclamate. Some of the amino acid positions crucial for activation of hTAS1R2+hTAS1R3 by neohesperidin dihydrochalcone are involved in the binding of allosteric modulators in other class C GPCRs, suggesting a general role of these amino acid positions in allosterism and pointing to a common architecture of the heptahelical domains of class C GPCRs.